Switching to Bictegravir, Emtricitabine, and Tenofovir Alafenamide in Virologically Suppressed Adults With Human Immunodeficiency Virus. (15th July 2020) - Sax, Paul E; Rockstroh, Jürgen K; Luetkemeyer, Anne F; Yazdanpanah, Yazdan; Ward, Douglas; Trottier, Benoit; Rieger, Armin; Liu, Hui; Acosta, Rima; Collins, Sean E; Brainard, Diana M; Martin, Hal; et al.
Abstract: Background: Bictegravir (B)/emtricitabine (F)/tenofovir alafenamide (TAF) is guideline-recommended treatment for human immunodeficiency virus type 1 (HIV-1). We evaluated whether people receiving dolutegravir (DTG) plus F/TAF or F/TDF (tenofovir disoproxil fumarate) with viral suppression can switch to B/F/TAF without compromising safety or efficacy, regardless of preexisting nucleoside reverse transcriptase inhibitor (NRTI) resistance. Methods: In this multicenter, randomized, double-blinded, active-controlled, noninferiority trial, we enrolled adults who were virologically suppressed for ≥6 months before screening (with documented/suspected NRTI resistance) or ≥3 months before screening (with no documented/suspected NRTI resistance) on DTG plus either F/TDF or F/TAF. We randomly assigned (1:1) participants to switch to B/F/TAF or DTG + F/TAF once daily for 48 weeks, each with matching placebo. The primary endpoint was proportion of participants with plasma HIV-1 RNA ≥50 copies/mL at week 48 (snapshot algorithm); the prespecified noninferiority margin was 4%. Results: Five hundred sixty-seven adults were randomized; 565 were treated (284 B/F/TAF, 281 DTG + F/TAF). At week 48, B/F/TAF was noninferior to DTG + F/TAF, as 0.4% (1/284) vs 1.1% (3/281) had HIV-1 RNA ≥50 copies/mL (difference, −0.7% [95.001% confidence interval CI, −2.8% to 1.0%]). There were no significant differences in efficacy among participants with suspected or confirmed prior NRTI resistance (n = 138). No participant had treatment-emergent drug resistance. Median weight change from baseline at week 48 was +1.3 kg (B/F/TAF) vs +1.1 kg (DTG + F/TAF) ( P = .46). Weight change differed by baseline NRTIs (+2.2 kg [F/TDF] and +0.6 kg [F/TAF], P < .001), with no differences between B/F/TAF and DTG + F/TAF. Conclusions: The single-tablet regimen B/F/TAF is a safe, effective option for people virologically suppressed on DTG plus either F/TDF or F/TAF, including in individuals with preexisting resistance to NRTIs. Clinical Trials Registration: NCT03110380. Abstract : Switching to bictegravir (B)/emtricitabine (F)/tenofovir alafenamide (TAF) was noninferior to dolutegravir (DTG) plus F/TAF at week 48, with high rates of virologic suppression. B/F/TAF is a safe, effective option for people virologically suppressed on DTG + F/tenofovir disoproxil fumarate or F/TAF, including individuals with preexisting resistance to nucleoside reverse transcriptase inhibitors.